Variations in the relative abundance of hemipteran species in different seasons and stages of rice growth depending on weather variations - Khalıd, Faıruz; Shaıkh Mazran, Noor Shuhaına; Rakıbe, Ismaıl; Mohammed, Muhamad Azmı; Aman Zuki, Ameyra; Yaakop, Salmah (Ankara University, 2024)
Rompin has played an active role in Malaysia's rice production for several decades. However, rice production faces a threat, particularly from the hemipteran insect pests. There is limited documentation on the abundance of these insects and their relationship with weather factors. Therefore, this study aimed to determine the abundance of hemipterans in different growth stages and to understand the effects of weather factors on their population in rice fields. The study was conducted in farmers' rice fields in Rompin, Pahang, Malaysia, during the main and off-season rice planting. Sweep nets, yellow sticky traps, and yellow pan traps were utilized in each plot. Trapped insects were identified based on the rice planting seasons and growth stages. The trends of weather factors such as rainfall, temperature, light intensity, and wind speed were analysed and correlated with insect abundance. A total of 23 023 individuals belonging to six families and eleven species of the hemipteran order were recorded. Nine of these species were pests, namely Leptocorisa oratorius (Fabricius) (2.05%), Maiestas dorsalis (Motschulsky) (41.93%), Nephotettix virescens (Distant) (1.52%), Nephotettix nigropictus (Stål) (0.03%), Scotinophara sp. (4.92%), Nilaparvata lugens (Stål) (28.18%), Sogatella furcifera (Horváth) (17.75%), Nezara viridula (Linnaeus) (0.01%) and Scotinophara coarctata (Fabricius) (2.88%). The other two species were predators, Cyrtorhinus lividipennis (Reuter) (0.55%) and Polytoxus fuscovittatus (Stål) (0.19%). Maiestas dorsalis, N. lugens, S. furcifera, and Scotinophara sp. were found in significantly (df=10, F=5.707, P<0.01) higher numbers and exceptionally high during rice's late vegetative and early reproductive stages. The maximum temperature significantly (R2>0.5 & P<0.05) increased during the main season, while wind speed increased significantly (R2>0.5 & P<0.05) during the off-season. Wind speed significantly positive correlated (r>0.5 & P<0.05) with N. virescens, S. furcifera, L. oratorius, and Scotinophara sp. On the other hand, rainfall exhibited a significant negative correlation (r>-0.5 &P<0.05) with L. oratorius. Various pest species and their high populations in this study pose a significant threat to plants due to their preferences for different plant parts and strata.